Role of ACE and ACE-2 in abrogated cardioprotective effect of ischemic preconditioning in ovariectomized rat heart - Vimal Kumar; Ahsas Goyal; Jeetendra Kumar Gupta (Universidade de São Paulo, 2022)
Abstract Ischemic heart disease is the leading cause of death in postmenopausal women. The activity of heart ACE increases whereas the activity of ACE-2 decreases after menopause. The present study was designed to investigate the role of ACE and ACE-2 in the abrogated cardioprotective effect of IPC in OVX rat heart. The heart was isolated from OVX rat and mounted on Langendorff's apparatus for giving intermittent cycles of IPC. The infarct size was estimated using TTC stain, and coronary effluent was analyzed for LDH, CK-MB, and nitrite release. IPC induced cardioprotection was significantly attenuated in the ovariectomized rat heart as compared to the normal rat heart. However, this attenuated cardioprotection was significantly restored by perfusion of DIZE, an ACE-2 activator, and captopril, an ACE inhibitor, alone or in combination noted in terms of decrease in myocardial infarct size, the release of LDH and CK-MB, and also increase in the release of NO as compared to untreated OVX rat heart. Thus, it is suggested that DIZE and captopril, alone or in combination restore the attenuated cardioprotective effect of IPC in OVX rat heart which is due to an increase in ACE-2 activity and decrease in ACE activity after treatment.